EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN TEKNIK COGNITIVE RESTRUCTURING DALAM MENINGKATKAN SELF-CONFIDENCE PADA SISWA KELAS VIII SMP NEGERI 3 KLATEN TAHUN AJARAN 2024/2025 - Dinda Keysha Alea; Eko Adi Putro; Ahmad Jawandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Dinda Keysha Alea. EFFECTIVENESS OF GROUP COUNSELING SERVICES USING COGNITIVE RESTRUCTURING TECHNIQUES IN IMPROVING SELF-CONFIDENCE IN EIGHTH GRADE STUDENTS AT SMP NEGERI 3 KLATEN IN THE 2024/2025 ACADEMIC YEAR. Self-confidence is an important aspect of student development. Cognitive restructuring emphasizes changing negative thought patterns into positive ones.The purpose of this study was to determine the effectiveness of group counseling services using cognitive restructuring techniques in improving self-confidence among eighth-grade students at SMP Negeri 3 Klaten in the 2024/2025 academic year.The research method used an experimental approach with a one-group pretest-posttest design. The research subjects consisted of 7 students selected using purposive sampling. The instrument used was a questionnaire that measured the level of students' self-confidence behavior before and after group counseling. Data obtained from analysis using the Wilcoxon test showed that there was an increase in the average score from 83.00 on the pretest to 91.57 on the posttest with a significance value of 0.018 < 0.05, so Ho was rejected and Ha was accepted. It can be concluded that there was a significant difference between before and after the treatment, which means that group counseling using the Cognitive Restructuring technique was able to increase the self-confidence of eighth-grade students at SMP Negeri 3 Klaten in the 2024/2025 academic year.